Prevalence of Methicillin-resistant Staphylococcus aureus (MRSA) Carrier in Hemodialysis Patients at Dr. Soetomo Academic General Hospital - Wicaksono, Eko Oktiawan; Tjempakasari, Artaria; Widodo, Widodo (Institute of Topical Disease Universitas Airlangga, 2020)
Chronic kidney disease (CKD) is now a global epidemic, and the prevalence is increasing worldwide. Hemodialysis is one of the ways to treat by kidney function replacement. Infection is the number two cause of death in patients with hemodialysis (HD). Methicillin-resistant Staphylococcus aureus (MRSA) is a common cause of bacteriemia in patients with dialysis. The epidemiological data of MRSA carriers in CKD in Indonesia are still scarce. This study was to determine the prevalence of MRSA carriers in patients at The Kidney and Hypertension Outpatient-clinic and Hemodialysis Installation at Dr. Soetomo Academic General Hospital, Surabaya Indonesia. The study design was descriptive-analytic with a cross- sectional study design. Sampling was collected consecutively. Data on the general characteristics of the research subjects will be analyzed using a Chi-Squared test. There were 150 CKD stage five patients included in this study, the number of patients has MRSA carrier were 6 (4%), among them, subjects underwent HD MRSA carrier were 2 subjects(2.7%), while for non-HD patients with MRSA were 4 subjects (5.3 %). There were no significant diï¬€erences in MRSA carriers between HD and non HD groups (p=0.404). Comorbid factors that accompany MRSA carriers are diabetes mellitus, hypertension, kidney stones, gout, and systemic lupus erythematosus (SLE). This study found, there were no significant diï¬€erences in the incidence of MRSA carriers in stage five CKD non HD or HD groups. MRSA colonization exists in stage five CKD suï¬€erers, so awareness of MRSA colonization